Drosophila melanogaster importin alpha1 and alpha3 can replace importin alpha2 during spermatogenesis but not oogenesis. - Mason, D Adam (2002)
Importin alpha's mediate the nuclear transport of many classical nuclear localization signal (cNLS)-containing proteins. Multicellular animals contain multiple importin alpha genes, most of which fall into three conventional phylogenetic clades, here designated alpha1, alpha2, and alpha3. Using degenerate PCR we cloned Drosophila melanogaster importin alpha1, alpha2, and alpha3 genes, demonstrating that the complete conventional importin alpha gene family arose prior to the split between invertebrates and vertebrates. We have begun to analyze the genetic interactions among conventional importin alpha genes by studying their capacity to rescue the male and female sterility of importin alpha2 null flies. The sterility of alpha2 null males was rescued to similar extents by importin alpha1, alpha2, and alpha3 transgenes, suggesting that all three conventional importin alpha's are capable of performing the important role of importin alpha2 during spermatogenesis. In contrast, sterility of alpha2 null females was rescued only by importin alpha2 transgenes, suggesting that it plays a paralog-specific role in oogenesis. Female infertility was also rescued by a mutant importin alpha2 transgene lacking a site that is normally phosphorylated in ovaries. These rescue experiments suggest that male and female gametogenesis have distinct requirements for importin alpha2.